2013
DOI: 10.1900/rds.2013.10.228
|View full text |Cite
|
Sign up to set email alerts
|

Metformin and Cancer

Abstract: ■ AbstractMetformin is well-known as an anti-diabetic drug, but it seems to possess anti-cancerous properties as well. Adenosine monophosphate-activated protein kinase (AMPK) is a highly conserved regulator of the cellular response to the presence of low energy in all eukaryotic cells. It is considered a key sensor of the balance of cellular ATP and AMP concentrations. LKB1 serine/threonine kinase is a divergent yet evolutionarily well-conserved kinase, biochemically sufficient to activate AMPK in vitro and ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 98 publications
(110 reference statements)
0
41
0
3
Order By: Relevance
“…Metformin is generally accepted as an anti-diabetic drug and is also considered a first-line treatment for type 2 diabetes (16). However, in previous years, numerous studies have confirmed that patients treated with metformin have lower incidence and mortality rates of various types of cancer, including lung cancer, breast cancer, pancreatic cancer and gastric cancer (5)(6)(7)(8). A study by Kim et al (7) reported that diabetic patients with no administration of insulin had a decreased incidence of gastric cancer when treated with metformin, compared with those who were not treated with metformin.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Metformin is generally accepted as an anti-diabetic drug and is also considered a first-line treatment for type 2 diabetes (16). However, in previous years, numerous studies have confirmed that patients treated with metformin have lower incidence and mortality rates of various types of cancer, including lung cancer, breast cancer, pancreatic cancer and gastric cancer (5)(6)(7)(8). A study by Kim et al (7) reported that diabetic patients with no administration of insulin had a decreased incidence of gastric cancer when treated with metformin, compared with those who were not treated with metformin.…”
Section: Discussionmentioning
confidence: 99%
“…However, the mechanism underlying the anticancer effects of metformin remain to be fully elucidated Previous studies have shown that, despite the complexity of the molecular signaling mechanisms of metformin, several critical molecules and pathways have been confirmed to be involved in this regulation, including the activation of AMPK (8,18), inhibition of mammalian target of rapamycin complex-1 (19), interruption of the crosstalk between insulin and insulin-like growth factor-1 receptor (20) and reductions in the expression of vascular endothelial growth factor and plasminogen activator inhibitor-1 (21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In patients with persistent hyperglycemia despite consequent use of oral antidiabetics treatment by subcutaneous insulin injections is the standard therapy used in clinical routine. 4 In the past few years, large epidemiological studies suggested a link between DM and antidiabetic drugs and several cancer entities including PCa (reviewed in [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%